Gone before goodbye [compact disc, unabridged] - Witherspoon, Reese, 1976-; Coben, Harlan, 1962- (Blackstone Publishing, 2025)
Maggie McCabe is a highly skilled and renowned Army combat surgeon. Upside down after a series of tragedies leads to her medical license being revoked, Maggie has lost her purpose but not her passion. At her lowest point, a former colleague offers her a job for an elite plastic surgeon. When a patient disappears, Maggie must flee or she will be the next to vanish.